Fatal Cryptococcus gattii genotype VGI infection in an HIV-positive patient in Barranquilla, Colombia - María Clara Noguera; Patricia Escandón; Elizabeth Castañeda (Revista do Instituto de Medicina Tropical de São Paulo)
ABSTRACT Cryptococcosis is a major invasive fungal disease related worldwide with the AIDS population. New reports of HIV/AIDS cases to the national public health surveillance system (SIVIGILA) in Colombia have shown that there is a growing community at risk of contracting cryptococcosis throughout the country who do not have access to ART. Even though the most prevalent species Cryptococcus neoformans is mainly associated with the HIV population, we report a fatal case of cryptococcosis in an AIDS patient in Barranquilla, associated with Cryptococcus gattii VGI, isolated from blood culture.